(untitled) (Journal of the College of Basic Education, 2022)
The symbol is one of the means used in the modern poem, which gives it an active role in poetrygiving the text a suggestive energy; So the Iraqi poet Ahmed Matar resorted to enriching his text with it, even a special oneimportant in the poem Al-Matariyya being a convenient means of satirizing reality; The form of a special poetic visionBy him, he reshaped and formulated it through his images; The language of the symbol has one of the loving expression methodsAnd expressive of his creative poetic experience of the poet. Ahmed Matar dealt with two types of symbols: they are natural symbols; and iconshumanity; Through them, he devised means that distinguished him from other poets of his generation until I became knownThose symbols done as rooms made .